Analysis of enzyme activity and the level of malondialdehyde in the saliva of children with gingivitis - Tričković-Janjić Olivera; Cvetković Tatjana; Apostolović Mirjana; Kojović Draginja; Kostadinović Ljiljana; Igić Marija; Šurdilović Dušan (Vojnosanitetski Pregled)
Introduction/Aim. By analyzing activity of some of the enzymes normally present in the saliva and the level of malondialdehyde in gingivitis, it is possible to estimate the functional condition of parodontium, and the examined parameters can be considered as biochemical markers of its functional condition. The aim of this paper was to examine activity of alanine aminotransferase, aspartate aminotransferase, gamma glutamyl transferase, lactate dehydrogenase and the level of malondialdehyde in the saliva of children affected with gingivitis, as well as the values of the mentioned parameters in relation to the level of the inflammation of gingiva. Methods. The research included 120 children at the age of 12.2 with permanent dentition. Löe and Silness gingival index was used to estimate the condition of gingiva, based on which the children were classified into four groups: the children with healthy gingiva (the control groups), the children with mild, moderate and severe inflammation of gingiva (the study group). Enzymes of the saliva were determined by the use of original tests and measured by the autoanalyser (Bio Systems A25, Spain). A modified method with tiobarbituric acid was used to determine malondialdehyde in nonstimulated mixed saliva. Results. The results of the examined enzyme activity and the level of malondialdehyde in the saliva of the study groups showed statistically considerably higher values for the level of malondialdehyde (p < 0.001), for the activity of aspartate aminotransferase and gamma glutamyl transferase (p < 0.01), as well as for alanine aminotransferase (p < 0.05) in comparison with the control group, whereas the activity of lactate dehydrogenase did not show a statistically significant increase. In relation to the level of the inflammation of gingiva, the results of the examination of the enzyme activity in the study groups showed statistically significantly higher values in the group with severe inflammation in comparison with those with mild, as well as the moderate inflammatory, except for the gamma glutamyl transferase, and in the group with moderate inflammation compared to that with the mild one, except for alanine aminotransferase. The results of the examination of the level of malondialdehyde in the saliva of the study groups did not show a statistically significantly increase in relation to the level of the inflammation of gingiva. Conclusion. There is a higher level of alanine aminotransferase, aspartate aminotransferase, gamma glutamyl transferase and lactate dehydrogenase enzyme activity together with the higher level of malondialdehyde in the saliva of children with gingivitis in comparison with the activity of the same enzymes and the level of malondialdehyde in the saliva of children without gingivitis. The activity of the examined enzymes in the saliva of children with gingivitis increases in relation to the intensity of the pathological process, whereas the level of malondialdehyde shows no significant difference in relation to the level of the inflammation of gingiva.